Rhetoric as art of eloquence in the ancient greek culture - Seiilbek, Saken; Zhunissova, Maira; Koshekova, Ainur; Kadyrov, Zhanbai; Duisebekova, Zhainagul (Opción, 2018)
Throughout the period of the ancient culture, rhetoric predetermined not only the style of speech, but also substantially views and behavior as life philosophy. Works of ancient speakers on rhetoric exerted huge impact on all further development of the theory of oratory; they made a significant contribution on development of practical eloquence. Speakers in the works open the problems relevant today. They were interested in a question: what is necessary for the good speaker, and drawn a conclusion that the perfect speaker must have natural talent, memory, to have skill and knowledge, to be an educated person and actor.